2011
DOI: 10.1177/0734242x11410114
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamics of indigenous bacterial communities associated with crude oil degradation in soil microcosms during nutrient-enhanced bioremediation

Abstract: Bacterial population dynamics were examined during bioremediation of an African soil contaminated with Arabian light crude oil and nutrient enrichment (biostimulation). Polymerase chain reaction followed by denaturing gradient gel electrophoresis (DGGE) were used to generate bacterial community fingerprints of the different treatments employing the 16S ribosomal ribonucleic acid (rRNA) gene as molecular marker. The DGGE patterns of the nutrient-amended soils indicated the presence of distinguishable bands corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Microbial population number is one of important biological indicators in oil contaminated sites since microbes play an important role in contaminants degradation [38,39]. Microbial populations of heterotrophic bacteria in the seven oil fields were determined by MPN (most probable number) method (Fig.…”
Section: Soil Microbial Populationsmentioning
confidence: 99%
“…Microbial population number is one of important biological indicators in oil contaminated sites since microbes play an important role in contaminants degradation [38,39]. Microbial populations of heterotrophic bacteria in the seven oil fields were determined by MPN (most probable number) method (Fig.…”
Section: Soil Microbial Populationsmentioning
confidence: 99%
“…Hydrocarbons interact with the environment and microorganisms determining the fate of the contaminant relative to their chemical nature and microbial degra-dative capabilities respectively. Provided the polluted has requisite values for environmental factors that influence microbial activities and there are no inhibitors of meta-bolism, there is a good chance that there will be a viable and active population of hydrocarbon utilizing micro-organisms in the environment (Chikere et al, 2011(Chikere et al, , 2012b. Considering the large quantity of oil going into the Niger Delta environment especially farmlands and rivers, the need to cleanup crude oil contaminated sites has become a key environmental issue (Vincent et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and case studies have shown that autochthonous bacterial communities are capable of adapting to oil contamination and degradation of oil-derived compounds (Acosta-González et al 2015; Oliveira et al 2013; Chikere et al 2012; Bento et al 2005). LH-PCR has been proved to be a sensitive method to monitor the successional changes in bacterial community (Yan et al 2016; Mikkonen et al 2014).…”
Section: Discussionmentioning
confidence: 99%